Survey instruments and the reports of consumption expenditures: evidence from the consumer expenditure surveys. (29th June 2015) - Battistin, Erich; Padula, Mario
Summary: The paper uses data from the consumer expenditure surveys to demonstrate that the mode of collection is important for the analysis of consumption data. We first show that population figures obtained with diaries markedly differ from figures obtained by using recall questions. We then exploit multiple measurements of food expenditure to identify the effects of the mode of collection on the distribution of reported consumption. Finally, we show how to combine information from multiple reports to obtain a single measure of total expenditure in consumer expenditure surveys. The paper concludes by offering guidelines for empirical analyses based on these data, and by providing an application of the methods proposed to the measurement of inequality and wellbeing.